Fish diversity of floodplain lakes on the lower stretch of the Solimões River - F. K. Siqueira-Souza; C. E. C. Freitas (Brazilian Journal of Biology)
The fish community of the Solimões floodplain lakes was studied by bimonthly samples taken from May 2001 to April 2002. These were carried out at lakes Maracá (03º51'33"S, 62º35'08,6"W), Samaúma (03º50'42,1"S, 61º39'49,3"W), and Sumaúma and Sacambú (03º17'11,6"S and 60º04'31,4"W), located between the town of Coari and the confluence of the Solimões and Negro rivers. Collections were done with 15 gillnets of standardized dimensions with several mesh sizes. We collected 1,313 animals distributed in 77 species, belonging to 55 genera of 20 families and 5 orders. Characiformes was the most abundant Order, with a larger number of representatives in the Serrasalmidae and Curimatidae. The most abundant species in the samplings were Psectrogaster rutiloides (132 individuals), Pigocentrus nattereri (115 individuals), and Serrasalmus elongatus (109 individuals). Lakes Samaúma, Sacambú, and Sumaúma were adjusted to logarithmic and lognormal series. The diversity exhibited an inverse gradient to the river flow, showing the highest diversity at Lake Sumaúma, followed by Samaúma, Sacambú, and Maracá. Species richness estimated through the jackknife technique ranged from 78 to 107 species.